Population-based study of early-onset neonatal sepsis in Canada. Issue 2 (24th April 2018) - Sgro, Michael; Kobylianskii, Anna; Yudin, Mark H; Tran, Dat; Diamandakos, Julia; Sgro, Jonathan; Campbell, Douglas M
Abstract: Objective: To determine the incidence, types of organisms and resistance patterns involved in early-onset neonatal sepsis in Canada. Study design: Early-onset neonatal sepsis cases were identified through the Canadian Paediatric Surveillance Program. Neonates were excluded if they were asymptomatic or if intracranial procedures preceded a positive cerebrospinal fluid culture. Results: One hundred and twenty-seven cases were identified (0.17 cases per 1000 live births). Group B Streptococcus accounted for 41.7%, Escherichia coli fo r 35.4%. Antibiotic resistance was present in 33.9% of all cases. 55.6% of E coli cases were resistant, most commonly to ampicillin. Infecting organism species were associated with gestational age, being very low birth weight, time at sepsis presentation, maternal antibiotic prophylaxis and rupture of membranes lasting over 18 hours. Group B Streptococcus was most common in term and E coli in preterm neonates. Twenty-two per cent of E coli cases presented after 48 hours, compared to 6% of Group B Streptococcus cases. Conclusion: We identify a lower rate of early-onset neonatal sepsis than historically suggested, with differing dominant organisms based on gestational ages and other factors, as well as high rates of resistance especially among E coli cases.